Youth Ministry An Inclusive Missional Approach - Nel, Malan (HTS Religion & Society Series, 2018)
This book aims at contributing to the scientific and academic discourse as regards to the 'what' and 'why' of youth ministry. Too often, youth ministry has been approached from a mainly practical point of view, almost asking how we keep young people off the streets. Its methodology has often not included the theological and theoretical presuppositions that lie behind this ministry. Previous scientific reflection has been determined by a one-dimensional and almost exclusive point of view. In comparison with existing literature, this book does not focus so much on the 'how' of youth ministry. It innovates a different approach. The book challenges the existing exclusive approach and develops an inclusive, congregational and missional understanding of and approach to youth ministry.From a particular perspective on the understanding the main objectives of Practical Theology, the author endorses the so-called movement of 'what is supposed to be going on'. He adds the outcome of an empirical round table discussion with some 16 leaders in this field on the descriptive and interpretive movements within the subject field: what is going on and why is it going on? The book will form the standard for any new research with regard to youth ministry. The book's contribution lies on the level of sound theological reasoning and argumentation (supported by many scholars) for an inclusive congregational understanding of ministry as an integral part of every congregation being missional in being and doing. Youth, children, adolescents and emerging adults, are just as integral a part of every congregation within which they live and serve.